Republic of Latvia : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Latvia. (IMF Staff Country Reports; Country Report, 2016)
This paper focuses on the key issues related to the economy of Latvia. Growth picked up somewhat last year despite a weak external environment. GDP growth rose to 2.7 percent, up about u percent over the previous year. However, growth is expected to slow slightly in 2016 to 2 1\2 percent. While Latvia continues to make steady economic progress, a key challenge will be to generate the growth necessary to sustain the pace of income convergence with Western Europe. Structural reforms will be required to improve state-owned enterprise governance and strengthen the business environment, upgrade public infrastructure, and modernize legal systems.